Kejadian Penyakit Busuk Buah Kakao (Phytophthora palmivora var. palmivora) di Desa Karlutu, Kecamatan Seram Utara Barat, Kabupaten Maluku Tengah - Christoffol Leiwakabessy; Esther D Masauna; Costanza Uruilal (JURNAL PERTANIAN KEPULAUAN, 2020)
The disease of cocoa fruit rot almost infecting all cocoa planting areas in Indonesia.The research aims to determine the disease incidence of fruit rot and its attack onthe cocoa crop in Karlutu village, North West Seram District. The research used acompletely random design block and repeated 3 times. Observations wereperformed on the people's cocoa crop in the village of Karlutu and taken 10 trees assamples for each replay. Subsequent fruit samples were carried to the laboratory andisolated using pin-set into petri-dish containing PDA media, then incubated for 48hours at a room temperature of 25-27 Â°c. The results of the study obtained theaverage highest disease incidence of cocoa fruit rot disease of 54% and the lowest(33%) in the village of Karlutu. Besides, the condition of cocoa farmer plantationthat is poorly maintained by local farmers causes the high damage caused by thisdisease. Thus, required strengthening local farmer knowledge about optimalcultivation of cocoa by implementing an effective strategy of integrated controlplant disease with an environmentally friendly approach.